Anomaly Detection in Network Security: Deep Learning for Early Identification - Patil, Rahul Manohar; Patil, Rajendra V.; Pagare, Umesh Bhimrao; Navandar, Rajesh Kedarnath; Mapari, Rahul; Bhowmik, Mahua; Deore, Shailesh Shivaji (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Network security anomaly detection is a crucial task in the contemporary digital environment. The requirement to spot deviations from the norm that might be signs of cyber dangers has risen dramatically as organisations depend more and more on interconnected networks for their operations. An overview of the main ideas, approaches, difficulties, and developments in the area of anomaly detection in network security are given in this abstract. Unusual patterns or behaviours that depart from accepted standards are known as anomalies. These behaviours might range from unauthorised access attempts to erratic data flows. Due to the dynamic and ever-changing nature of cyber threats, detecting these abnormalities is a challenging process. Traditional rule-based systems frequently have a hard time keeping up with the constantly evolving strategies of hostile actors. As a result, to improve the accuracy and adaptability of anomaly detection, researchers have resorted to machine learning and deep learning approaches. Unsupervised and supervised machine learning techniques have become effective tools for anomaly identification. Without labelled data, unsupervised techniques like clustering and isolation forests can find unexpected abnormalities. Supervised algorithms use labelled anomalies in past data to train models that can discriminate between legitimate and harmful behaviour. Convolutional neural networks and recurrent neural networks are two deep learning techniques that enable the automated learning of complicated patterns from data, allowing for the identification of very intricate abnormalities. In order to give a thorough knowledge of network behaviour, hybrid approaches that integrate statistical insights with machine learning techniques have gained popularity. These methods seek to reduce false positives and negatives, crucial factors in actual security operations. Additionally, the use of explainable artificial intelligence (XAI) approaches increases transparency, making it easier for security analysts to understand how complicated models make decisions. Handling skewed datasets, preventing adversarial assaults on detection models, and assuring scalability for real-time monitoring are challenges in anomaly detection. Researchers are coming up with new ideas through investigating transfer learning to enhance model generalisation, graph-based methods for representing networks, and the creation of reliable assessment measures. In conclusion, anomaly detection in network security continues to be a rapidly evolving area that is essential to protecting digital ecosystems. Statistical techniques and cutting-edge machine learning algorithms work together to identify risks and vulnerabilities in a variety of ways. Researchers and practitioners must remain flexible as cyber threats change, relying on technology and human knowledge to create a safe and resilient digital future.